2018
DOI: 10.1016/j.acap.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perspectives of Barriers to Physical Activity in Urban Schoolchildren With Asthma

Abstract: A complex, multilevel set of barriers to PA exist in children with asthma. Addressing these barriers by involving stakeholders at the family, school, and community levels may improve PA levels in children with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
(43 reference statements)
1
24
0
4
Order By: Relevance
“…The outcome of this misinterpretation may be that children restrict their activity levels and subsequently have lower fitness ability and develop exercise avoidance behaviours (18,19). As has been previously documented in the literature, participants in this study suggested that restricting exercise may also develop from fear of exercise-induced asthma attacks (8). Research has shown that parental anxiety can lead to children developing avoidance behaviours in asthma-threat scenarios (20).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The outcome of this misinterpretation may be that children restrict their activity levels and subsequently have lower fitness ability and develop exercise avoidance behaviours (18,19). As has been previously documented in the literature, participants in this study suggested that restricting exercise may also develop from fear of exercise-induced asthma attacks (8). Research has shown that parental anxiety can lead to children developing avoidance behaviours in asthma-threat scenarios (20).…”
Section: Discussionsupporting
confidence: 59%
“…The US National Asthma Education and Prevention Program recommends weight management to improve overall health and asthma control in both adults and children (7). Yet most paediatric weight management programmes are not tailored to the unique needs of living with asthma, such as addressing parental anxieties that arise from breathlessness when exercising and the child's perceptions of exercise parameters (8,9). So far, the limited weight management programmes designed specifically for children living with asthma have shown promising results in improving asthma control and reducing weight (10).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study of elementary school teachers demonstrated few were aware that students with asthma need not avoid exercise [76]. Part of parental concern appears to be driven by worry regarding lack of symptom perception in children and lack of trust in school asthma management [77]. Other barriers have also been identified that prevent this group of patients in engaging with physical activity: fear of exacerbating symptoms, with patients with more severe disease more likely to view exercise as detrimental [78], and children's poor adherence to treatment also identified as barriers [77].…”
Section: Barriers To Exercise In Children With Asthmamentioning
confidence: 99%
“…Parents of children with asthma have identified barriers unique to the child's medical condition. Challenges and lack of trust for asthma management, exacerbation of the condition due to a lack of the child's awareness of symptom onset, and nonadherence to required treatment or medications were of significant concern (12). It has also been reported that parents and health care providers have different perceptions regarding the physical activity restrictions appropriate for children with complex cardiac conditions (13).…”
Section: Abstract: Cardiology; Habitual Physical Activity; Parent Permentioning
confidence: 99%